AN ANALYSIS OF STUDENTS' SPEAKING ANXIETY IN AN EFL CLASS AT MUHAMMADIYAH UNIVERSITY OF METRO - Amirudin Latif; Syaifudin Latif Darmawan; Kurnia Hakim (Journal of English Education and Entrepreneurship (JEEP), 2023)
This study aims to identify the fundamental causes of anxiety and create treatments to reduce it. This survey was done since a lot of pupils don't know what worries are or how to handle them. Using a qualitative technique, the researcher looked at and discussed the data on student anxiety. This study included 26 students from the sixth semester of the English Education Department at Muhammadiyah University of Metro. The researcher employed an interview, an FLCAS questionnaire created by Horwitz in 1986 that had been modified to fit the research focus, and an observation to gather data. According to the survey results, there are five levels of anxiety among students, ranging from low to high. The next step was to choose 10 students from the low anxiety and high anxiety groups for interviews to determine the reasons and treatments for anxiety. According to the study's findings, 15.3% of students had low anxiety, 3.84% of students had very low anxiety, 30.7% of students had moderate anxiety, 34.6% of students had very high anxiety, and 15.3% of students had severe anxiety. After analysing the data of the interviews, the study identified six traits that contributed to students' worry: poor English proficiency, misinterpretation anxiety, low self-esteem, evaluation anxiety, lack of preparation, and excessive test anxiety. Researcher also came up with a number of strategies that may be utilized to help students feel less anxious, including changing one's perspective, being well-prepared, practicing to boost one's confidence and English proficiency, and finally, being brave. Additionally, the researcher detailed the recommendations that other researches could have used. The next researchers should determine from various angles of the speaking anxiety, including the learning setting, the history of the students, and instructor insight.